Internalization of Humanistic Values Through Local Wisdom at Sunan Drajat Islamic Boarding School Lamongan as A Pillar of Religious Moderation - Maftuhah, Maftuhah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Pondok Pesantren Sunan Drajat is a traditional Islamic educational institution that not only functions as a center for transmitting religious knowledge but also plays a vital role in shaping students’ character based on humanistic values. The object of this study is the process of internalizing humanistic values practiced through the pesantren’s local wisdom. The aim of this research is to examine how these values are internalized and established as a pillar of religious moderation. This study employs a qualitative approach using literature study and descriptive analysis methods. The findings reveal that values such as compassion, solidarity, mutual cooperation, tolerance, simplicity, and respect for differences are implemented in the educational traditions and social activities of the students. The discussion emphasizes that this internalization fosters moderate and adaptive students who are capable of becoming agents of peace in multicultural societies. In conclusion, the local wisdom of Pesantren Sunan Drajat plays a strategic role in strengthening religious moderation and serves as a model of Islamic education relevant to contemporary challenges.